2020
DOI: 10.24914/jeb.v23i2.3293
|View full text |Cite
|
Sign up to set email alerts
|

Determinan pertumbuhan ekonomi berkelanjutan wilayah induk dan pemekaran di kawasan timur Indonesia

Abstract: Penelitian ini bertujuan untuk mengetahui faktor-faktor penentu pertumbuhan ekonomi di kawasan timur Indonesia setelah pemerintah menerapkan kebijakan otonomi daerah di Indonesia. Penelitian ini meliputi wilayah induk dan wilayah pemekaran pada kawasan timur Indonesia. Penelitian ini menggunakan data sekunder dari statistik Indonesia. Penelitian ini menggunakan data cross-section pada tahun 2017 yang mencakup 230 kabupaten dan kota. Penelitian ini menggunakan least square dummy variable dalam menganalisis data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Garis Kemiskinan adalah perwujudan kemampuan seseorang atau keluarga dalam suatu masyarakat untuk memenuhi kebutuhan dasar hidup pada suatu waktu di lokasi tertentu guna menjalani kehidupan secara layak. Seseorang akan tergolong miskin secara absolut apabila memiliki pendapatan di bawah garis kemiskinan sehingga tidak mampu mencukupi kebutuhan dasanya [13]. Sedangkan secara relatif, kemiskinan dilihat dari dimensi ketimpangan antar kelompok masyarakat.…”
Section: Pendahuluanunclassified
“…Garis Kemiskinan adalah perwujudan kemampuan seseorang atau keluarga dalam suatu masyarakat untuk memenuhi kebutuhan dasar hidup pada suatu waktu di lokasi tertentu guna menjalani kehidupan secara layak. Seseorang akan tergolong miskin secara absolut apabila memiliki pendapatan di bawah garis kemiskinan sehingga tidak mampu mencukupi kebutuhan dasanya [13]. Sedangkan secara relatif, kemiskinan dilihat dari dimensi ketimpangan antar kelompok masyarakat.…”
Section: Pendahuluanunclassified
“…However, there are other factors that also contribute to increasing economic growth, namely regional income from the taxation and trade sectors. Hutajulu et al (2020) the results showed that the determinants of economic growth in 230 districts and cities in Eastern Indonesia are the variables of poverty, human development, inequality, and fiscal decentralization. The results of their research showed that there are several factors that have a significant relationship to GRDP in the province of West Java, namely: the local revenue variable or .PAD, the transfer income variable, other income variables, and the level of independence of the West Java region (Ayu & Septiani, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Several researchers have conducted research related to the determinants of economic growth as social and economic indicators at both national and regional levels in various regions in Indonesia, such as (Garibaldi & Hidayat, 2014;Agusalim, 2016;Maqin & Sidharta, 2017;Ayu & Septiani, 2019;Nabut & Sinabutar, 2021;Sipahutar, Anjelina, Andriyani, & Yani, 2021;Wicaksono, Triwahyuningtyas, & Aminda, 2021;Panjawa, Islami, & Sugiharti, 2020;Lubis & Izzah, 2020, Wulandari, Badriah, & Kadarwati, 2019 who has researched the determinants of economic growth in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing concern that the focus of activities development and growth is dominated by the Western and is compared to Eastern Indonesia (Hutajulu, Panjawa, Islami, & Sugiharti, 2020;Nugraha, Wicaksono, & Wijaya, 2017;Panjawa et al, 2018;Riphat, Setiawan, & Damayanty, 2016). Based on the report about Evaluation of The Proliferation of Administrative Region in Indonesia by Bappenas (2008), the origin regions and the control regions consistently showed better results in all areas of focus (such as economic growth, regional fiscal management, public services and regional government personnel) compared to the new autonomous regions.…”
Section: Introductionmentioning
confidence: 99%